Les Églises unie, anglicane et catholique et la communauté anglo-québécoise: portrait et enjeux contemporains - Wilkins-Laflamme, Sarah (University of Ottawa (Canada), 2010)
Using annual statistics from the United, Anglican and Catholic Churches as well as demographic data from Quebec and Canada, the present thesis details the results of a series of quantitative analyses concerning the evolution of church indicators since the 1970s within the English-speaking community of Quebec. Data regarding religious affiliation, church attendance, membership and rites of passage (baptisms, professions of faith, confirmations, marriages and funerals) are also the object of comparisons with similar statistics from the rest of Quebec and Canada in order to establish the particularities of Anglo-Quebecers in this matter. The entirety of the results show three main axes which distinguish tendencies of decline from those of relative stability: differences between denominations (Protestantism-Catholicism), between linguistic communities (Anglophone-Francophone) and between regions (East-West). Anglo-Quebecers resemble more often than not English Canada regarding religious indicator tendencies from the three Christian churches being studied. Declines, especially protestant, in the English-speaking community are sometimes lesser than those in Ontario and in the West, but greater than those in the Atlantic region. These results are interpreted according to a theoretical framework allowing for the existence of several stories of secularization, dialoging most notably with the sociological works of David Martin, Daniele Hervieu-Leger and Raymond Lemieux --- experts regarding the link between church and national community as well as religious identity. In summary, new data is detailed and interpreted in order to contribute, in a modest but pertinent way, to the field of Sociology of Religion in Quebec and in Canada. An in depth examination of the relationship between Anglo-Quebecers and their three main Christian churches also allows to distinguish in many regards this population from other Quebecois and Canadian ethno-linguistic communities.
Keywords: Religion, General.; Sociology, Demography.